Studying the resistivity imaging of practical phantoms with common ground current injection technique in electrical impedance tomography. (1st January 2014) - Bera, Tushar Kanti; Nagaraju, J.
Surface electrodes are essentially required to be switched by analogue multiplexers operating with a set of parallel digital data for boundary data collection in electrical impedance tomography (EIT). A 16 electrode EIT system needs 16-bit parallel digital data to operate the multiplexers. More electrodes in an EIT system require more digital data bits. In this paper, a common ground current injection method is proposed for a 16 electrodes EIT system to switch the electrodes with reduced number of digital data. Common ground method needs only two 16:1 multiplexers operating with only 8-bit parallel digital data. Boundary data are collected from practical phantoms by injecting a constant current using common ground method. Resistivity images are reconstructed in EIDORS and the results are compared with the images obtained in opposite current pattern. Reconstructed images obtained with common ground method are found similar to the images obtained with the conventional opposite current pattern.